COMPLETION THYROIDECTOMY FOR DIFFERENTIATED THYROID CARCINOMA - Ullah, Niamat; Khan, Qaisar; Said, Muhammad; Afridi, Habib ur Rehman; Ahmad, Naseer (Journal of Postgraduate Medical Institute, 2011)
Objective: The purpose of this study was to evaluate the morbidity and mortality of completion thyroidectomy for differentiated thyroid carcinoma. Material and Methods: This study was conducted in the department of ENT Head and Neck surgery and General Surgery Lady Reading Hospital, Peshawar over a period of two years from December 2005 to December 2007. Forty patients of differentiated thyroid carcinoma underwent completion thyroidectomy. The patients with thyroid nodule underwent pre op thyroid ultrasonography, FNAC, biochemical examination and indirect examination of the vocal cord. Results: Forty patients were included in this study, in which four were males and thirty six were females, age ranged from 27 to 62 years, with an average of 27 ± 2.6. The indications for initial operation were a solitary thyroid nodule in 36 (90%), patients, multi-nodular goiter 3(7.5%) and Grave's disease 1(2.5%). The initial operation for solitary thyroid nodule included unilateral lobectomy in 33 patients and hemithyroidectomy in 3, subtotal thyroidectomy in 3 patients of multi nodule goiter and near total thyroidectomy in 1 patient of Grave's disease. Total morbidiy was 12.5% and comprised of transient hypoparathyroidism in 3(7.5%), permanent hypoparathyroidism in 1 (2.5%) transient Recurrent Laryngeal Nerve (RLN) palsy in 1 (2.5%) patient. There was no mortality. Conclusion: Completion thyroidectomy can be performed safely with morbidity of 12.5% and no mortality.